Assessment of the Strength of the Frame of an Electric Locomotive Bogie of the 2UZ ELR Series (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this article, a computational model of the bogie frame of an 2UZELR electric locomotive was created, and its strength state was studied based on the finite element method (FEM). The computational model is compiled in the SolidWorks program, and the geometry, load, and boundary conditions are based on real operating conditions. Based on the research results, the stress distribution and deformation zones of the bogie frame were determined.